The influence of technological treatments on physical and chemical structure of wine - Babich, Irina (My University, 2013)
A necessary condition for the competitiveness of domestic wine in the international consumer market is to further increase the wine quality with extension of terms of the guaranteed stability up to 1.5 years.Gelatin and bentonite are ones of the most common purifying and stabilizing preparations, which are widely used in the practice of winemaking. In this context, it is an important task of testing imported auxiliary products of new generation and their adaptation to the domestic winemaking.
Keywords: wine cloudiness; бентоніт; желатин; помутніння вина; кафедра біотехнології продуктів бродіння і виноробства